Polis: Enciclopédia Verbo da Sociedade e do Estado - dir. João Bigotte Chorão (Verbo, 1997)
1.º vol.: A - C, 1480 Colunas; 2.º vol.: D - F, 1590 Colunas; 3.º vol.: G - L, 1316 Colunas; 4.º vol.: M - P, 1772 Colunas; 5.º vol;. Q - Z, 1734 Colunas.